Analysis of SMEs Readiness in the Implementation of Internet of Things to Support the Smart City Concept - Anestesia Purba, Arini; Sibatuara, Janter; Acantha Manapa Sampetoding, Eliyah; Sirinti Pongtambing, Yulita; Isabella, Mayati; Dwi Wantira, Amanda; Desfelia Ciciolini Sidabutar, Elizabeth (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
This study aims to analyze the readiness of MSMEs based on existing model artifacts related to implementing the Internet of Things (IoT) to support the concept of smart cities. In this study, the Design Science Methodology understanding model from Hevner is used in analyzing the views of SMEs actors. The results of the questionnaire processing from 147 MSME actors found that the obstacles to IoT implementation are the production process that is still manual, the production machine is still not automatic/manual, difficulties in capital, the communication media used is still email and telephone, and the production work environment is not safe and still integrated with the house. These obstacles can be used as input in implementing the Internet of Things in MSMEs. The recommendations given in the implementation of the Internet of Things for SMEs are to provide capital loans in collaboration with Regional Banks, determine regional superior products to be used as Pilot Projects in the implementation of the Internet of Things, collaborate with local governments for the development of MSMEs in funding and appropriate technology to increase the productivity and quality of SMEs production.